Determining the Real Causes of Financial Crisis in Islamic Economic Perspective: ANP Approach - . Ascarya (Institute for Research and Community Empowerment (LPPM TAZKIA), 2015)
Objective – The purpose of this study is to determine the real causes of financial crisis from Islamic economic perspective.Methods - This study applies Analytic Network Process (ANP) to determine the real causes of financial crisis from Islamic economic perspective to be able to formulate the real solutions to end financial crisis.Results - The ANP results show that the real causes of financial crisis from Islamic economic perspective are Social Instability (EXTERNAL FACTOR), Speculation (MISBEHAVIOR), Ineffective Fiscal System (UNSUSTAINABLE FISCAL SYSTEM), Hedonism (MISBEHAVIOR), Fractional Reserve Banking System (UNSTABLE MONETARY SYSTEM), Political Instability (EXTERNAL FACTOR), Corruption (POOR GOVERNANCE), Interest Rate (UNSTABLE MONETARY SYSTEM), Fiat Money (UNSTABLE MONETARY SYSTEM), and the Wrong Man in the Wrong Place (POOR GOVERNANCE). These main real causes should be removed gradually in order to systematically and gradually improve the stability of financial system so that financial crisis will not reappear again and again in the future.Conclusions - Financial crisis would not happen under Islamic economic system if all Allah’s laws in financial dealings were followed. Financial crisis in conventional economic system could be prevented or lessened by gradually adopting Islamic economic and finance laws and regulations, partly or fully, especially the main pillars of Islamic financial system, namely the prohibition of ribā (usury or interest), prohibition of maysir (gambling and game of chance or speculation) and prohibition of gharar (excessive uncertainty), in their many forms.